2021
DOI: 10.1021/acs.energyfuels.1c03032
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Spherical α-Fe2O3 for Highly Efficient Gaseous Arsenic Capture in Simulated Flue Gas Under a Wide Temperature Range

Abstract: Arsenic emitted from coal-fired flue gas poses a threat to human health and the ecological environment due to its high toxicity and bioaccumulation. In this work, the microscopic spherical α-Fe2O3 sorbent was prepared by a one-step hydrothermal method to effectively capture arsenic in the flue gas. The effects of reaction temperature, sulfur dioxide (SO2), nitric oxide (NO), oxygen (O2), and inlet arsenic concentration on its adsorption performance were investigated. The results showed that the most suitable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The adsorption of arsenic by CaO occurs mainly by chemisorption, and arsenic adsorbed in the reaction product is As 5+ . 11 Elevated temperatures promote the capture of arsenic by CaO, and the same phenomenon was also observed in the capture process of CeO 2 /CaO. CeO 2 /CaO can provide enough active sites for arsenic capture than untreated CaO.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The adsorption of arsenic by CaO occurs mainly by chemisorption, and arsenic adsorbed in the reaction product is As 5+ . 11 Elevated temperatures promote the capture of arsenic by CaO, and the same phenomenon was also observed in the capture process of CeO 2 /CaO. CeO 2 /CaO can provide enough active sites for arsenic capture than untreated CaO.…”
Section: Resultsmentioning
confidence: 62%
“…The capture trends for CeO 2 /CaO and CaO are similar, with increasing temperatures promoting the trapping of arsenic, with CeO 2 /CaO capture significantly higher than CaO in the same temperature range. The adsorption of arsenic by CaO occurs mainly by chemisorption, and arsenic adsorbed in the reaction product is As 5+ . Elevated temperatures promote the capture of arsenic by CaO, and the same phenomenon was also observed in the capture process of CeO 2 /CaO.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The results of the DFT study by Zhang et al [50] also showed that As 2 O 3 (g) could form eight stable adsorption structures on the (001) surface of Fe 2 O 3 with a minimum adsorption energy of 275.52 kJ mol À1 . One-step hydrothermal preparation was used by Zhao et al [51] to create a tiny, spherical α-Fe 2 O 3 adsorbent, and the effects of reaction temperature, nitric oxide (NO), oxygen (O 2 ), nitric dioxide (NO), sulfur dioxide (SO 2 ), and inlet arsenic concentration on the adsorption performance were investigated. The effect of its temperature on the capture of As 2 O 3 (g) by α-Fe 2 O 3 is shown in Figure 2 [51].…”
Section: Adsorption Of Arsenic By A-fe 2 O 3 Adsorbentmentioning
confidence: 99%
“…Arsenic stays with a particular matter, which goes to the environment as ash. There are a few technologies to control its release, such as coal washing before combustion, arsenic capture sorbent, 2–4 and so forth. Besides, atmosphere and temperature have a great effect on arsenic distribution during the reaction 5 .…”
Section: Introductionmentioning
confidence: 99%